Perkembangan dan Peranan TV Berbasis Dakwah Islam - Effendy, Erwan; Aisyah, Nur; Manurung, Rahma Sari; Adelisa, Wahyu (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to analyze the development and role of television based on Islamic da'wah. The type of method used in this study is a qualitative method using secondary data. The results showed that in implementing the Islamic da'wah program through television media, there were several da'wah methods used, namely: the Talking Method, the Insertion Method, and the Infiltration Method. In learning, television provides three important roles, namely the role in providing cognitive, affective and psychomotor benefits. Da'wah through television must contain a lot of information and ways of delivering it so that the da'wah delivered via television can be accepted and interested in many people, namely by relating to four main things, namely, updating the concept of da'wah, expanding and strengthening networks or collaboration with institutions engaged in da'wah , strengthening primary and secondary funds to fund da'wah programs, and increasing the quality and quantity of preachers and preachers, especially those that are already popular on television media. Keywords: Television, Da'wah, Islam, Role, Development